A novel method to decorate Au clusters onto graphene via a mild co-reduction process for ultrahigh catalytic activity. Issue 1 (30th November 2016) - Song, Zhongqian; Li, Weiyan; Niu, Fushuang; Xu, Yuanhong; Niu, Li; Yang, Wenrong; Wang, Yao; Liu, Jingquan
Abstract : A mild co-reduction strategy is exploited to fabricate Au clusters on reduced graphene oxide with low Au loadings for high catalytic activity. Abstract : To achieve high catalytic activity and stability with low noble-metal loadings on special supports has triggered much research interest in the past few years. Herein, a mild co-reduction strategy was exploited to fabricate glutathione decorated Au clusters (with a size of ∼1.4 nm) on reduced graphene oxide (Au@HSG-rGO) with low Au loadings and high catalytic activity in an aqueous medium. The resultant Au@HSG-rGO complex exhibited 20.8 times higher catalytic activity than Au nanoparticle supported graphene for catalysis of the reduction of 4-nitrophenol (4-NP). The Au@HSG-rGO was packed in a filtering platform to afford a fixed-bed system, with which the catalytic conversion reached 96.03% for 0.2 mM 4-NP solution at a flow rate of 1 mL min −1 . In addition, the poly(2-(dimethylamino) ethyl acrylate) modified Au@HSG-rGO (Au@HSG-rGO-PDMAEA) via π–π stacking interactions exhibited good recyclability and tunable catalytic activity and only showed slight loss of activity after recycling five times. The PDMAEA served as forest-like shelters to efficiently protect the Au@HSG clusters from aggregation and also endowed the system with enhanced stability and temperature-controlled catalytic activity. Meanwhile, the Au@HSG-rGO showed excellent electrocatalytic activity for the oxygen reduction reaction in alkaline electrolytes. This simple, economical and mild strategy could be generalized to the preparation of other metal cluster complexes for broad catalytic and analytical applications.